General Correspondence - Ogilvie, W. G (My University, 1962)
Correspondence about Manley, Yallahs Valley, the hills of St. Thomas
9 pgs. Typescript, Handwritten, sepia-toned, in good condition.
Keywords: Ogilvie W. G. - Correspondence; Yallahs Valley - Jamaica